Embracing the wild profusion: A Foucauldian analysis of the impact of healthcare standardization on nursing knowledge and practice. (27th June 2018) - Slemon, Allie
Abstract: Standardization has emerged as the dominant principle guiding the organization and provision of healthcare, with standards resultantly shaping how nurses conceptualize and deliver patient care. Standardization has been critiqued as homogenizing diverse patient experiences and diminishing nurses' skills and critical thinking; however, there has been limited examination of the philosophical implications of standardization for nursing knowledge and practice. In this manuscript, I draw on Foucault's philosophy of order and categorization to inform an analysis of the consequences of healthcare standardization for the profession of nursing. I utilize three exemplars to illustrate the impact of the primacy of standardized thinking and practices on nurses, patients and families: pain assessments using the 0‐10 pain scale; patient triage emergency departments through the Canadian Triage and Acuity Scale; and determination of cause of death within the context of the current opioid crisis. Through each exemplar, I demonstrate that standardization reductively constrains nursing knowledge and the health and healthcare experiences of patients and populations. I argue that the centrality of standardization must be re‐envisioned to embrace the complexity of health and more effectively and meaningfully frame nursing knowledge and practice within healthcare systems.